MENINGKATKAN KEMAMPUAN MENGENAL BILANGAN PADA ANAK KELOMPOK A MELALUI PERMAINAN KANTONG BILANGAN DI PAUD AZ-ZAHRA’ LEKOK - Latifah; Windasari, Indriana Warih (Al-ATHFAL: Jurnal Pendidikan Anak, 2023)
This research aims to improve the number recognition game using number bags. This research uses Classroom Action Research, the subjects in this research are Group A children at PAUD AZ-ZAHRA' LEKOK, totaling 16 children. Based on the results of children's evaluation analysis regarding increasing the ability to recognize numbers through the number bag game, in the pre-cycle it was 15% for 3 children, then after using number recognition through the number bag game the percentage achieved in cycle I was 70% for 11 children, and the cycle II, the percentage increased, the percentage increased to 90% for 15 children. Therefore, it can be concluded that the number recognition activity is through the number bag game for Group A children at PAUD AZ-ZAHRA'LEKOK. Key words: games, number bags, recognizing number.